ChemInform Abstract: Direct Synthesis of Hexagonal NaGdF4 Nanocrystals from a Single‐Source Precursor: Upconverting NaGdF4:Yb3+, Tm3+ and Its Composites with TiO2 for Near‐IR‐Driven Photocatalysis. Issue 39 (September 2015) - Chen, Ying; Mishra, Shashank; Ledoux, Gilles; Jeanneau, Erwann; Daniel, Marlene; Zhang, Jinlong; Daniele, Stephane
Abstract A single source precursor, NaGd(tfa)4(diglyme) is prepared from a THF solution of Na(tfa), Gd(tfa)3(H2O), and diglyme (room temperature, 5 h; 83% yield).